Minimal Length Schrödinger Equation with Harmonic Potential in the Presence of a Magnetic Field - H. Hassanabadi; E. Maghsoodi; Akpan N. Ikot; S. Zarrinkamar (Advances in High Energy Physics)
Minimal length Schrödinger equation is investigated for harmonic potential in the presence of magnetic field and illustrates the wave functions in the momentum space. The energy eigenvalues are reported and the corresponding wave functions are calculated in terms of hypergeometric functions.